MFS-LDA: a multi-feature space tag recommendation model for cold start problem. Issue 3 (5th September 2017) - Masood, Muhammad Ali; Abbasi, Rabeeh Ayaz; Maqbool, Onaiza; Mushtaq, Mubashar; Aljohani, Naif R.; Daud, Ali; Aslam, Muhammad Ahtisham; Alowibdi, Jalal S.
Abstract : Purpose: Tags are used to annotate resources on social media platforms. Most tag recommendation methods use popular tags, but in the case of new resources that are as yet untagged (the cold start problem), popularity-based tag recommendation methods fail to work. The purpose of this paper is to propose a novel model for tag recommendation called multi-feature space latent Dirichlet allocation (MFS-LDA) for cold start problem. Design/methodology/approach: MFS-LDA is a novel latent Dirichlet allocation (LDA)-based model which exploits multiple feature spaces (title, contents, and tags) for recommending tags. Exploiting multiple feature spaces allows MFS-LDA to recommend tags even if data from a feature space is missing (the cold start problem). Findings: Evaluation of a publicly available data set consisting of around 20, 000 Wikipedia articles that are tagged on a social bookmarking website shows a significant improvement over existing LDA-based tag recommendation methods. Originality/value: The originality of MFS-LDA lies in segregation of features for removing bias toward dominant features and in synchronization of multiple feature space for tag recommendation.